"All over the place": A case study of classroom multitasking and attentional performance. (November 2015) - Hassoun, Dan
Media multitasking has become a contested practice in many college classrooms. Students increasingly split their attentions between lecture and personal media, while educators largely view the new screens as fostering disengaged and distracted forms of conduct. Together, teachers and students have developed a series of strategies governing the proper practice of multitasking during lecture. Using interviews and ethnographic field observations, I examine how these strategies of media use operate within one undergraduate classroom. Drawing from this case study, I argue that multitasking reveals a complex series of negotiations between teachers, students, and their co-present environment. Examining these negotiations provides not only a snapshot of how media attention is practiced within the classroom but also suggests ways for instructors to respond to the rise of new technologies within their own classes.